Measuring Business Process Complexity Using Cyclomatic Number - Sharifah Intan Eriyatty, Syed Mansor (2004)
This research study focuses on the measurement of the business process complexity. The business process that are chosen are the Bachelor of Information Technology (BIT) Student Course Registration and Knowledge Management International Conference and Exhibition (KMICE) Participant Registration. Both business processes are chosen because the processes do not relate with any external agent aside Universiti Utara Malaysia as it will bring difficulties in capturing the business process information. On the other hand, these two business processes are used to compare the complexity value of the registration process. Method that is used to measure the complexity value is by using cyclomatic number. This cyclomatic number is a method which combines the graph-theory and mathematical technique to measure complexity. At the first place, this research analyze the activities that involved in one business process from the beginning to the end. Then, it is mapped into a UML notation which is in an activity diagram. The activity diagram will give an overview of a business process. It will then be transformed to the cyclomatic graph according to the connectivity matrix derived from the cyclomatic graph. Finally, calculation of the complexity value by using the cyclomatic number is automated. To draw a conclusion, this research will help us to indicate the value of a business process complexity. It is also hoped to help organization on order to measure their business process complexity and thus help in the re-structuring process. However, in the future, it is hoped that business process from any other discipline aside from academic will measure their business process complexity using the automated tool developed.